Reliability-based design of interventions in deteriorated timber structures - Sousa, Hélder S.; Neves, Luís C. (Taylor & Francis, 2018)
When accommodating new uses or mitigating the consequences of deterioration, the strength increase of existing structures is significantly more onerous than a similar increase at the design stage of new structures. The safety methods prescribed in current standards were defined for the design of new structures and are frequently conservative for the assessment and repair of existing structures. This work will introduce the fundamental aspects of structural reliability and their application in the context of existing timber structures regarding the use of target reliability indices. First, the fundamental methods of structural reliability are introduced. The use of reliability methods requires the use of more detailed information in respect with material properties, loads, and model uncertainty. The main sources of such information are described. After overviewing the fundamental methods of structural reliability, methods to introduce additional information, namely results of non-destructive tests in the structural assessment are discussed. Finally, the intervention on a timber structure will be analyzed, within a case study, by considering different repair scenarios that lead to discussions on different suitable safety thresholds for existing and repaired structures.